Constructivism in Indonesia-Malaysia Relations on the One Channel System - Rifky, Muhammad Alif (GoAcademica Research & Publishing, 2025)
This article explores the implementation of the One Channel System (OCS) in Indonesia-Malaysia bilateral labor migration policy through the lens of constructivism. This study examines how international norms on migrant worker protection, particularly those outlined in ILO conventions, are internalized in migration policies, as well as key challenges in the effective implementation of OCS, such as institutional coordination, economic interests, and technological barriers. Using a qualitative approach, the research analyzes the tension between normative commitments and material considerations faced by both countries. The findings show that while Indonesia prioritizes the protection of its migrant workers, Malaysia's reliance on informal recruitment mechanisms like the Maid Online System (SMO) weakens the achievement of OCS goals. This duality highlights the limitations in norm socialization and the challenges of aligning global labor standards with domestic realities. This study contributes to the understanding of constructivist theory in migration policy by emphasizing the intersection of international norms, state identity, and pragmatic realities. The significance of this research lies in its ability to provide policy recommendations to improve the implementation of OCS and its contribution to the development of constructivism in migration policy, showing how international norms and state identity interact in labor migration governance.